The “7 Up” Intersectionality Life Grid: A Tool for Reflexive Practice - Fuller, Kay (Frontiers in Education, 2020)
Feminist epistemology ensures women's ways of seeing are central to research purpose and process. In particular, feminist standpoint theory recognizes epistemic privilege. Situated knowledge, what is known and the ways it can be known, is shaped by the positionality of knowledge producers. A reflexive approach prompts feminist researchers to reflect deeply on the situation and perspective of their position in relation to the focus of research. The research process with women school leaders of diverse heritages led the author to re-examine her personal and professional story as a white woman of working class origins, raised, educated and working in education as an educator, school leader, initial teacher educator and scholar in the UK. The author developed a heuristic device for reflection as a '7 Up' intersectionality life grid to think about her life in education at seven year intervals in relation to the experience of learning, educating, leading and researching in the context of unequal gender, class and race relations in wider society. This re-examination enabled her to deepen understanding of her positionality as it related to work in the field of women, gender and educational leadership. In this critically reflexive autoethnography, I report on reflections guided by the seven year intervals of the ‘7 Up’ framework at nine points (birth to 56 years old) as reflexivities of complacency, reflexivities that discomfort and reflexivities that transform. I draw on Bourdieu’s concepts of misrecognition and symbolic violence, and for the first time in work on intersectionality in educational leadership, hysteresis to theorize about complicity with white supremacy, white privilege and white fragility. The ‘7 Up’ intersectionality life grid tool has capacity to prompt the critically reflective and transformative self-narrative work essential to feminist scholars. It is also a valuable tool for critical reflexivity among women and men students, educators, leaders and learners of diverse heritages across national contexts in education. Engaging with reflexivities that discomfort has the potential to transform self-narratives, construct relationships and carry out and interpret research differently.